Systematic Literature Review: Riset pelecehan seksual pada anak di Indonesia - Siti Sarah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
Children are the successor of the future of the nation. Sexual abuse in children can destroy the future of children, even the nation. This case must be resolved immediately. Research is an important way of providing information and various field findings to be followed up in policy formulation as well as concrete steps in an effort to real problems. The research aims to provide in-depth information regarding research on child sexual abuse in Indonesia, particularly in the realm of research methods and study focus. The research used the SLR (Systematic Literature Review) method. Data was collected by documenting and reviewing all articles related to child sexual abuse in 2020 - 2022. They are 37 articles from accredited national and international journals obtained from Google Scholar and SINTA. The study shows that research related to child sexual abuse in Indonesia uses many methods. The qualitative is the most popular method. Conversely, the mix-method is the minimum research. The research also analyzes the focus of the problem of sexual abuse in children in three groups. They are preventive, curative efforts, and case analysis. As a result, preventive means are the most studied, and case analysis broadly is the lowest.